The long-run impact of the 1968 Washington, DC civil disturbance - Stan Veuger; Leah Brooks; Jonathan Rose; Daniel Shoag (American Enterprise Institute (AEI), 2020)
This paper studies the urban development impacts of the civil disturbances that took place in Washington, DC following the assassination of Martin Luther King Jr. in 1968.
Keywords: A; 330; capital investment; Civil rights; development; Economic development; Washington D.C.